Kesadaran Etis Guru terhadap Kode Etik Profesi dalam Era Digital - Muhammad Luthfi Ma'sum; M. Alif Hidayat; Shibghah Al-Mujaddidi; Dykhi Fernandez; Aditya Insani (ASSUNNAH PRESS, 2026)
The development of digital technology has brought significant changes to teachers’ professional practices while simultaneously presenting new challenges in the implementation of professional ethics in education. Learning processes that increasingly take place in digital environments require teachers not only to possess pedagogical competence and digital literacy but also a strong ethical awareness in applying professional codes of ethics. This study aims to analyze the level of teachers’ ethical awareness of professional codes of ethics within the context of education in the digital era. The study employs a descriptive qualitative approach combining a literature review with limited field data collection. The literature review was conducted through the examination of scholarly journals and documents on teachers’ professional codes of ethics, while field data were obtained through the distribution of questionnaires and limited interviews with teachers. This approach was adopted to gain a comprehensive understanding of teachers’ perceptions and practices regarding professional ethics in digital learning environments. The findings indicate that teachers’ ethical awareness ranges from moderate to good; however, its implementation in digital contexts continues to face various challenges. The results reveal a gap between normative understanding of professional codes of ethics and teachers’ professional practices in the use of digital media. The main challenges identified include limited understanding of digital ethics, weak professional boundaries, and the influence of school culture as well as the dynamics of technological development. Therefore, this study emphasizes the importance of strengthening teachers’ professional ethics as a foundation for professionalism and educational integrity in the digital era.